THE INFLUENCE OF CURRENT RATIO, RETURN ON ASSET, DEBT ASSET RATIO, AND TOTAL ASSET TURNOVER ON FINANCIAL DISTRESS. Case study of Manufacturing Companies in the Coal Mining Sub Sector Listed on the Indonesia Stock Exchange in 2019-2021 - Muhammad Reynadi Mahardika; Ferry Mulyawan (SEAN Institute, 2023)
The goal of this analysis is to determine the relationship between a number of economic variables (such as the Current Ratio [CR], Return on Asset [ROA], Debt Asset Ratio [DAR], and Total Asset Turnover [TATO]) predict financial hardship among businesses in the coal mining sector between 2019 and 2021). Purposive sampling was used to pick the sample, and as a result, 27 businesses satisfied the sample requirements. Panel data is used in the data analysis approach. According to the findings of the hypothesis test, Financial Distress is significantly influenced by Total Asset Turnover (TATO), Debt Asset Ratio (DAR), Return on Asset (ROA), and Current Ratio (CR). In contrast to the Current Ratio (CR), Return on Asset (ROA), and Total Asset Turnover (TATO), sthe Debt Asset Ratio (DAR) is highly predictive of financial hardship.